2001
DOI: 10.1115/1.1429931
|View full text |Cite
|
Sign up to set email alerts
|

Automatic Assembly Feature Recognition and Disassembly Sequence Generation

Abstract: This paper describes a system for the automatic recognition of assembly features and the generation of disassembly sequences. The paper starts by reviewing the nature and use of assembly features. One of the conclusions drawn from this survey is that the majority of assembly features involve sets of spatially adjacent faces. Two principle types of adjacency relationships are identified and an algorithm is presented for identifying assembly features which arise from “spatial” and “contact” face adjacency relati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(30 citation statements)
references
References 38 publications
0
30
0
Order By: Relevance
“…The existing assembly feature definitions in the literature are also domain specific. Sung, Corney, and Clark [8] concluded that what these definitions have in common is that assembly features are the regions of an assembly that help improve the efficiency for the assembly planning. Assembly features can be classified based on different criteria, such as mating relationship, number of connecting form features (surface, edge, corner, etc.…”
Section: Basic Assembly Featuresmentioning
confidence: 97%
“…The existing assembly feature definitions in the literature are also domain specific. Sung, Corney, and Clark [8] concluded that what these definitions have in common is that assembly features are the regions of an assembly that help improve the efficiency for the assembly planning. Assembly features can be classified based on different criteria, such as mating relationship, number of connecting form features (surface, edge, corner, etc.…”
Section: Basic Assembly Featuresmentioning
confidence: 97%
“…Assembly features have been widely used to improve the efficiency of the assembly design and planning process (Sung, Corney, and Clark 2001;van Holland and Bronsvoort 2000). In this research, only the geometric attributes of a part are considered as assembly features.…”
Section: Online Assembly Modellingmentioning
confidence: 99%
“…Shahwan [16] extracted interfaces using bounding boxes of components in a DMU to filter non-adjacent components and subsequently check for geometric interactions. Sung [19] used an octree approach to locate assembly interactions for disassembly sequence generation. These interfaces are readily available in the non-manifold cellular model.…”
Section: Transferring Analysis Attributes Between Analysis Models At mentioning
confidence: 99%